Food and feeding habits of yellowfin tuna, Thunnus albacares (Bonnaterre, 1788) caught by handline around Payao in Moro Gulf - Barut, Noel C. (U.P. in the Visayas, 1987)
This study with the qualitative and quantitative analyses of the stomach contents of adult yellowfin tuna caught by handline operated in conjunction with payao in Moro Gulf for a period of one year, from November 1983 to October 1984. A total of 620 stomachs, taken from 403 males and 217 females, were analyzed. The average total weight of stomach contents of male yellowfin was 427 g while that of the female was 405 g. the average total food intake of male yellowfin was 8.1 g/kg and 10 g/kg for the female. However, there is no significant difference in the food consumption between sexes. The most important food items of female yellowfin, as determined by the index of relative importance (IRI), are skipjack (993), fish species belonging to the family Balistidae (302), yellowfin (771), and squid (208) ; those of the male are skipjack (1065) yellowfin (913), squid (343) and crab (154). The daily meal of female yellowfin is estimated at 2073 g, 768 g of which consists of prey organisms, 1075 g of chum and 230 g of digested food. Male yellowfin consumes about 2,185 g of food per day consisting of 937 g prey, 967 g chum and 281 g digested food. Predation by adult yellowfin caught under payao is higher on juvenile skipjack and yellowfin than on other foodfishes.